LINGUACULTURAL AND ETHNOLINGUISTIC CHARACTERISTICS OF ONOMASTIC UNITS IN UZBEK AND ENGLISH (Journal of Universal Science Research, 2023)
This article deals with the semantics of phraseological units consisting mainly of antroponyms. It is known that antroponyms form the largest lexical-semantic group of onomastic units. Therefore, in this article, proper nouns have been analyzed in the English and Uzbek language from a linguacultural point of view using several examples.